DESIGN, DEVELOPMENT AND CHARACTERIZATION OF EXTENDED RELEASE MULTIUNIT PARTICULATE SYSTEM OF ANTI-INFLAMMATORY DRUG (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Multi unit particulate system has long been employed to improve the bioavailability of drugs. Mesalamine pellets were prepared by Coating drug solution on sugar sphere followed by various functional coating. The influence of rate controlling membrane made up of Eudragit RSPO and Eudragit RLPO in combination with delay release polymer coating with Eudragit L100 in different proportions on drug release kinetics was studied. Pellets were for the various parameter like Physical characteristics, assay and in-vitro dissolution profile. The study confirmed that mesalamine can be delivered by multi unit particulate system into lower part of intestine. Optimized formulations were evaluated for In-vitro release profile. The optimized formula was stable at accelerated storage condition 40°C / 75 % RH. Prepared Pellets can be used in the treatment of the ulcerative colitis.